Harsh Noise Wall: Transformation of Sound and Space - Statkauskaitė, Greta (Semiotika, 2024)
This article describes the authentic experience of a harsh noise wall, revealing the changing relationship between space and sound. The article focuses on the listener’s experience while listening to this subgenre of music live. To identify the elements that contribute to the creation of meaning, the analysis includes paramusical factors that are semiotically related, though not structurally specific to a particular musical discourse. To investigate this issue Philip Tagg’s semiotic method of music analysis is used. It is based on video recordings of performances by noise artists The Rita (USA), Merzbow (JPN) and Vomir (FR), with accompanying listener reviews. The study examines how listening mode, listening location, listener activity and cultural location alter the listener’s experience. Harsh noise wall, which first appears to be a homogeneous genre, becomes a heterogeneous object of musical and sensory experience. This article develops the idea that not only can the performance space affect the sound and the listener’s experience, but there is also the potential for this relationship to be reversed, as sound transforms the space and changes the visual notion of it.